Analysis of Hydration and Optimal Strength Combinations of Cement-Limestone-Metakaolin Ternary Composite - Xiao-Yong Wang (Advances in Materials Science and Engineering)
Metakaolin (MK) is an aluminosilicate pozzolan material and can contribute to property development of concrete due to the pozzolanic reaction. Limestone (LS) powder presents the dilution effect, nucleation effect, and chemical effect on hydration of cement. When metakaolin and limestone are used together, due to the additional chemical reaction between the aluminum phase in MK and limestone, the synergetic benefit can be achieved. This study presents a hydration model for cement-limestone-metakaolin ternary blends. Individual reactions of cement, metakaolin, and limestone are simulated separately, and the interactions among cement hydration, limestone reaction, and metakaolin reaction are considered through the contents of calcium hydroxide and capillary water. The hydration model considers the pozzolanic reaction of metakaolin, chemical and physics effects of limestone, and synergetic effect between metakaolin and limestone. Furthermore, the gel-space ratio of hydrating concrete is calculated using reaction degrees of binders and concrete mixtures. The strength development of ternary blends is evaluated using the gel-space ratio. Based on parameter analysis, the synergetic effect on strength development is shown and the optimal combinations of cement-limestone-metakaolin ternary blends are determined.